Metrology of Pedestrian Locomotion and Slip Resistance 2003
DOI: 10.1520/stp10741s
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Slip Resistance Measurements between Two Tribometers Using Smooth and Grooved Neolite®-Test-Liner Test Feet

Abstract: Differences in slip resistance measurements under dry and wet conditions on the same smooth walkway surface may occur when testing with a Neolite®4-Test-Liner (NTL) test foot using the PIAST [Slip Test Mark II] and VIT [English XL] tribometers. To investigate the causes of these differences, two sets of NTL test feet (smooth and grooved) for each instrument were cut from the same piece of material. Slip-resistance measurements were made under both wet and dry conditions. The same operator was used for each tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…The results of our tribometer measurements were consistent with the conclusions of previous studies in that different tribometers give varied COF values for the same surface (4–14). For example, wet Delrin ® was categorized as being very slippery because of its ability to cause 12 of 14 subjects to slip; yet, the tribometers measured a range of COF from 0.06–0.69 for this surface.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of our tribometer measurements were consistent with the conclusions of previous studies in that different tribometers give varied COF values for the same surface (4–14). For example, wet Delrin ® was categorized as being very slippery because of its ability to cause 12 of 14 subjects to slip; yet, the tribometers measured a range of COF from 0.06–0.69 for this surface.…”
Section: Discussionsupporting
confidence: 92%
“…While many manufacturers claim that their tribometers can predict the probability of safe human ambulation on a walkway surface, numerous studies have shown that different tribometers yield different measurements of friction for the same flooring material (4–14). These friction differences approach an order of magnitude in some cases (5,9) and are often pronounced in the presence of a contaminant (15).…”
mentioning
confidence: 99%
“…The results of our tribometer testing are consistent with prior studies that have demonstrated that different tribometers give different COF values for the same surface (4–15). In the current study, wet porcelain was categorized as “moderately slippery” as 15 of 20 subjects slipped when walking across it; yet the range of COF measurements from the 11 tribometers spanned from 0.19 to 0.62 for this surface.…”
Section: Discussionsupporting
confidence: 91%
“…To date, no tribometer model or mechanical test to measure COF relevant to human ambulation has been universally accepted. The fact that the measurement of friction is a function of both the material being tested and the measuring system itself explains why several studies have shown that different devices yield different COF measurements for the same surface (4–15). For example, a study of nine tribometers demonstrated an extremely wide range of COF values for the same surface when tested under wet conditions (0.06–0.69) (14).…”
mentioning
confidence: 99%